Healing from the Past, into the Future: Socio-Cultural & Health Remediation for a Holistic Wellness Facility in Riverlea Township (Extension) - McCulloch, Claude Martin (University of the Witwatersrand, Johannesburg, 2024)
The Witwatersrand Mining Basin has been in existence since 1852, which is astonishingly more than a century old. It is the world’s largest gold and uranium basin and has created extraction from over 120 mines stretching from the East to the West of Johannesburg. It is an integral part and the backbone of Johannesburg’s economy. However, regardless of how much mining has boosted the economy, it has not played a sustainable role with the health of the citizens of Johannesburg. This is largely because of radioactive chemicals within the pyrite basin, holding 600 000 tons of uranium, amongst other chemicals as well (Liefferink, 2022). These radioactive chemicals are spread from the mining basin into the surrounding environment via windblown dust (Coetzee et al., 2008). Monitoring of these occurrences have shown that this dust is inhalable due to its structure and particle size, that being either PM 2,5 or PM 10. These happen at residential settings and have exceeded the levels of occupational health standards. A link is suggested from (Nkosi et al., 2015) between the respiratory issues amongst residents that live in communities next to mine tailings & waste facilities. These communities are exposed and have an increased prevalence of ‘chronic respiratory symptoms’ compared to other communities (Van Wyk, 2013). There are currently 585600 people living in communities next to mine tailings according to the 2011 census. (Kneen et al., 2015). The community I will be conducting my research will be in the Township of Riverlea, located in the South-West of Johannesburg. Riverlea is in close proximity to industrial areas and mine dumps. Research has shown that harmful pollutants can from these areas can have negative effects such on the respiratory system, as the particles are airbourne (Makene, 2007). Built in 1963 during Apartheid, ‘coloured’ residents were forcibly removed from other parts of the city and given new homes by the government. The township is conveniently located 500m away from the mine dumps, thus making it a high exposure zone to airborne dust pollution (Kneen et al., 2015). The respiratory diseases in Riverlea are caused from environmental problems. To relate this Architecturally, I research that social and cultural problems may be a symptom towards the residents being unhappy about their environment. This unhappiness and deals with the ‘Sense of Place’ for the resident’s and I believe, alters their social and cultural behaviour, hence many of these communities suffer from poverty, drugs, and crime (Najafi et al., 2011). This can be done using the design methods of Salutogenic design, which promotes healthy living and creates better places that can reduce stress, encourage physical activity, and afford opportunities for socializing, enhancing the general daily health and wellbeing of people (Cushing et al., 2020). I aim to design a holistic wellness facility that remediates the social, cultural and environmental problems which contests the current narrative of the context - that being poverty and respiratory disease.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Deterioration; Remediation; Contesting; SDG-3: Good health and well-being